2013
DOI: 10.5194/acp-13-9119-2013
|View full text |Cite
|
Sign up to set email alerts
|

Tethered balloon-borne aerosol measurements: seasonal and vertical variations of aerosol constituents over Syowa Station, Antarctica

Abstract: Tethered balloon-borne aerosol measurements were conducted at Syowa Station, Antarctica, during the 46th Japanese Antarctic expedition (2005–2006). Direct aerosol sampling was operated from near the surface to the lower free troposphere (approximately 2500 m) using a balloon-borne aerosol impactor. Individual aerosol particles were analyzed using a scanning electron microscope equipped with an energy dispersive X-ray spectrometer. Seasonal and vertical features of aerosol constituents and their mixing states w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(91 citation statements)
references
References 64 publications
5
85
1
Order By: Relevance
“…The summertime ExCl À chloride may be derived from volatile chloride that is displaced from sea-salt aerosols in the atmosphere during summer. This process has been observed to be more extensive during summer than winter due to the presence of acids and higher temperatures [Hara et al, 2013;Jourdain and Legrand, 2002], so volatile chloride is not expected to contribute significantly to ExCl À during winter. It is not expected that significant amounts of chloride would mix between summer and winter layers via diffusion or wind pumping in the snowpack given the high snow accumulation rates.…”
Section: 1002/2013jd020720mentioning
confidence: 99%
See 2 more Smart Citations
“…The summertime ExCl À chloride may be derived from volatile chloride that is displaced from sea-salt aerosols in the atmosphere during summer. This process has been observed to be more extensive during summer than winter due to the presence of acids and higher temperatures [Hara et al, 2013;Jourdain and Legrand, 2002], so volatile chloride is not expected to contribute significantly to ExCl À during winter. It is not expected that significant amounts of chloride would mix between summer and winter layers via diffusion or wind pumping in the snowpack given the high snow accumulation rates.…”
Section: 1002/2013jd020720mentioning
confidence: 99%
“…The sea ice source for aerosol with depleted Na + only occurs in winter, because the salt water brine above the sea ice must reach temperatures below À8°C for mirabilite precipitation to occur [Marion et al, 1999]. Fractionated sea-salt aerosol particles depleted in SO 4 2À [Abram et al, 2013 and references therein;Wagenbach et al, 1998a] and Na + [Hara et al, 2012[Hara et al, , 2013 have been observed to be abundant during Antarctic winter and attributed to mirabilite precipitation and a sea ice source. The prevalence of the sea ice source of sea-salt aerosol versus the open ocean source remains the subject of ongoing research, however [e.g.…”
Section: 1002/2013jd020720mentioning
confidence: 99%
See 1 more Smart Citation
“…For sample analysis, single particle analysis takes longer than bulk analysis. Therefore, few previous investigations have used single particle analysis (Parungo et al, 1979;Yamato et al, 1987a, b;Artaxo et al, 1992;Mouri et al, 1999;Hara et al, 1995Hara et al, , 2005Hara et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…soot and organics) (Kerminen et al, 2000;Legrand et al, 2001;Jourdain et al, 2008;Preunkert et al, 2008;Udisti et al, 2012). To better understand the origins of these constituents and the chemical reactions that occur on aerosol particles, single-particle analyses of Antarctic aerosols have been done (Parungo et al, 1979;Artaxo et al, 1992;Hara et al, 1995Hara et al, , 2005Hara et al, , 2013Mouri et al, 1999). More recently, Hara et al (2014) showed that most sea-salt particles in the continental region near the coast were modified with acidic sulphur species such as H 2 SO 4 and CH 3 SO 3 H. In contrast, other, non-sulphurous acidic species (likely HNO 3 ) contributed markedly to sea-salt modification in inland areas during the traverse.…”
Section: Introductionmentioning
confidence: 99%